Absolutisme Negara dan Lembaga Agama: Pasca Aufklärung di Eropa Barat - Kristiyanto, Eddy (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2005)
Along her history, the Catholic Church has hardly been able to get rid of political interests and power. The struggle to do so had in fact led her to even deeper involvement in the political world. Particularly in the ear after the Enlightenment the Church was more and more subordinated to the state by means of various juridical measures. The tensions between the state and the church, however, more often than not turned out to be a blessing in disguise, for thereby the Church was compelled to revisit her essential mission: to deal only with the moral and religious dimension of the civil society. It is this mission which calls for the Church to be continuously involved in the human affairs.